Pharyngeal penetration complicated by pneumomediastinum and surgical emphysema: a rare pediatric case report - Al Droubi, Belal; AlKatheeri, Rana; Salih, Esameldin; AlQaydi, Maryam Ali; Alsamri, Mohammed (Frontiers in Pediatrics, 2025)
Oropharyngeal injuries in young children, though common, carry the potential risk of serious complications. Here, we describe a rare case of a toddler with a minor penetrating injury in the hypopharynx leading to perforation, surgical emphysema, and pneumomediastinum. A 2-year-old boy was brought to the emergency department with noisy breathing and shortness of breath that started after a traumatic injury with a pencil in the mouth. He was found to have tachycardia, tachypnea, and grunting, but no stridor or retractions. A brief oral exam showed a blackish discoloration in the posterior pharyngeal wall, and crepitations were palpated on the neck. Imaging revealed extensive subcutaneous emphysema and a defect in the posterior oropharyngeal wall. He underwent surgical repair of the pharyngeal defect and was later discharged in stable condition. This case highlights the need for vigilance in assessing oral impalement injuries in children, as such injuries can lead to significant complications. Early detection and management are crucial to prevent severe outcomes. The case underscores the importance of careful clinical and radiological evaluation in managing pediatric oral impalement injuries.